The Use of Scrapbook Media in Mathematics Learning for Elementary School Students - Sarah Marwa Nabila; Berta Apriza; Karsoni Berta Dinata (LPPM Undiksha, 2025)
Mathematics is a basic science that not only teaches numbers and calculations but also trains logical, analytical, systematic, and critical thinking skills in solving contextual problems related to everyday life. This study examines the effectiveness of using scrapbook media in mathematics learning in elementary schools through the Systematic Literature Review (SLR) method. The literature search focused on the first keyword,